Cloning and characterization of a fourth human lysyl oxidase isoenzyme. - Mäki, J M (2001)
We report here the complete cDNA sequence and exon-intron organization of the human lysyl oxidase-like (LOXL)3 gene, a new member of the lysyl oxidase (LO) gene family. The predicted polypeptide is 753 amino acids in length, including a signal peptide of 25 residues. The C-terminal region, residues 529-729, contains a LO domain similar to those in the LOX (the first characterized LO isoenzyme), LOXL and LOXL2 polypeptides. It possesses the putative copper binding sequence, and the lysine and tyrosine residues that form the lysyltyrosyl quinone cofactor. The N-terminal region, which is similar to that in LOXL2 but not those in LOX and LOXL, contains four subregions similar to scavenger receptor cysteine-rich domains and a putative nuclear localization signal. Recombinant LOXL3, expressed in HT-1080 cells, was secreted into the culture medium but was not detected by immunofluorescence staining in nuclei. The LOXL3 mRNA is 3.1 kb in size and is expressed in many tissues, the highest levels among the tissues studied being seen in the placenta, heart, ovary, testis, small intestine and spleen.